Occurrence of Tocols in Foods: An Updated Shot of Current Databases - Alessandra Durazzo; Amirhossein Nazhand; Massimo Lucarini; Amélia M. Delgado; Maryna De Wit; Kar Lin Nyam; Antonello Santini; Mohamed Fawzy Ramadan (Journal of Food Quality)
Tocols are present in various foods, mostly in fruits and in plant seeds. Edible oils are the most important natural dietary sources of tocopherols and tocotrienols, collectively known as tocols. Tocopherols and tocotrienols are considered beneficial for their antioxidant effect which impacts on prevention of different health conditions. This perspective is addressed to give an updated picture of the tocol occurrence in foods. Moreover, the current state of the art of tocols in updated databases is explored and commented outlining their importance and future trends.